Pelaksanaan Remedial Teaching dalam Proses Pembelajaran PAI di SMA Negeri 2 Bukittinggi - Chindy Maretta (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study was motivated by the 2013 curriculum decision that requires students to complete their learning. Students who have not completed or have not yet completed their learning must take remedial classes. Based on this fact, the author was interested in providing a detailed description of this problem through descriptive qualitative field research using data from Islamic Education teachers of grade XII at SMAN 2 Bukittinggi during the first daily test of the odd semester of the 2019/2020 academic year, supported by interviews with students who participated in the remedial teaching program. To obtain data for this paper, the author observed the implementation of remedial learning by Islamic Education teachers of grade XII at SMAN 2 Bukittinggi during the first daily test in the odd semester of the 2019/2020 academic year. supported by interviews with Islamic Education teachers and reinforced by interviews with students involved in the remedial teaching program. From the research conducted, it was described that the implementation of remedial learning can be carried out in three stages of activities, namely preliminary activities in the form of activities that identify student problems and determine learning difficulties as well as plan solutions. The second activity is the core activity, which is the implementation of remedial learning itself and the re-measurement of the learning achievements of students who participate in remedial learning. The third activity is the closing activity, which is a re-evaluation and diagnosis of the results of remedial learning.